Samband félagsfælni og áfengisfíknar. Áhrif félagsfælni á edrúmennsku og AA-fundarsókn - Katrín Árnadóttir 1987- (2012)
Alcohol addiction is a vast problem in Iceland, where it is currently expected that between 10 and 22% of people will meet the diagnostic criteria for alcohol addiction at some stage in their lives. Individuals suffering from social phobia appear to be especially at risk. Epidemiological studies show that these people are up to three times more likely to be diagnosed as alcoholics than those not suffering from social phobia. The aim of this study was to explore the temporal relationship between social phobia and alcohol addiction, and the effects of suffering from comorbid social phobia and alcohol addiction in the frequency of sobriety and AA-attendance. This study was retrospective, using data from a study undertaken by SÁÁ and DeCODE genetics in Iceland. The study surveyed 900 participants and their families who had previously gone through treatment at SÁÁ. 72 of these participants met the diagnostic criteria for social phobia. It was predicted that social phobia would temporally precede alcohol addiction and, more specifically, that in the majority of cases the age of onset of social phobia would precede that of alcohol addiction. It was also predicted that participants suffering from comorbid social phobia would be less likely to attend AA-meetings than those who did not, and also that these participants would manage to abstain from alcohol for less time afterwards. The results of the study confirmed that the age of onset for social phobia preceded that of alcohol addiction, this being true in 71,4% of cases. The results also showed that the participants suffering from comorbid social phobia and alcohol addiction were able to abstain from alcohol for considerably less time than those not suffering from social phobia. No significant difference was found regarding the frequency of AA-attendance of the participants. Áfengisfíkn er mikið vandamál Íslandi og er talið að 10-22% líkur séu á því að einstaklingur mæti greiningarviðmiðum fyrir áfengisfíkn einhverntímann á ævinni. Einstaklingar sem þjást af ...